Nickel hyperaccumulation is independent of the leaf economics spectrum, although it may be linked to plant water balance in an ultramafic plant community from Sabah (Malaysia) - Celestino Quintela-Sabarís; Michel-Pierre Faucon; Béatrice Gervais-Bergeron; Sukaibin Sumail; Antony van der Ent; Rimi Repin; John Sugau; Reuben Nilus; Thomas Rigaudier; Guillaume Echevarria; Sophie Leguédois (Plant and Soil, 2025)
Background and aims Nickel (Ni) hyperaccumulators are a group of plants able to store elevated amounts of this element in their leaves. Some studies indicate that hyperaccumulation may be associated with traits favouring fast resource capture or with traits favouring nutrient and water conservation, but there is no evidence for the role of nickel hyperaccumulation in the leaf economics spectrum. Our study aims to assess the differences in the leaf economics spectrum between Ni hyperaccumulators and non-hyperaccumulators. Methods We have conducted a field study involving five hyperaccumulators and ten non-hyperaccumulators growing on the same ultramafic community in Sabah (Malaysia). We measured two structural and seven chemical leaf traits and computed a Principal Component Analysis, which was complemented by a test of the phylogenetic signal of each trait and linear mixed models to assess the influence of each leaf trait on nickel accumulation. Results Our analyses inferred three principal components that reflected the main environmental constraints that shape the resource acquisition strategies of the studied ultramafic plant community: leaf economics spectrum, hyperaccumulation and water-use efficiency, and calcium to magnesium balance. Moreover, the linear mixed models indicated that carbon isotope discrimination and potassium concentrations had a significant effect on Ni accumulation, suggesting that nickel might replace partially potassium in its role in plant water balance. Conclusion Overall, the data suggest that in the community studied, Ni hyperaccumulation is independent of the leaf economics spectrum and related to plant water economy. More studies with other hyperaccumulator plants are needed to confirm these findings.

Metal uptake and tolerance in hyperaccumulator plants: Advancing phytomining strategies - Fariha Nafeesa Md Fadzil; Mohd Azrul Naim Mohamad; Rimi Repin; Zakuan Azizi Shamsul Harumain (Rhizosphere, 2024)

Recovery of ultramafic soil functions and plant communities along an age-gradient of the actinorhizal tree Ceuthostoma terminale (Casuarinaceae) in Sabah (Malaysia) - Celestino Quintela-Sabarís; Etienne Auber; Sukaibin Sumail; Jean-François Masfaraud; Michel-Pierre Faucon; Françoise Watteau; Ramez F. Saad; Antony van der Ent; Rimi Repin; John Sugau; Reuben Nilus; Guillaume Echevarria; et al. (Plant and Soil, 2019)

Apparent annual survival estimates of tropical songbirds better reflect life history variation when based on intensive field methods - Thomas E. Martin; Margaret M. Riordan; Rimi Repin; James C. Mouton; William M. Blake (Global Ecology and Biogeography, 2017)
Aim Adult survival is central to theories explaining latitudinal gradients in life history strategies. Life history theory predicts higher adult survival in tropical than north temperate regions given lower fecundity and parental effort. Early studies were consistent with this prediction, but standard‐effort netting studies in recent decades suggested that apparent survival rates in temperate and tropical regions strongly overlap. Such results do not fit with life history theory. Targeted marking and resighting of breeding adults yielded higher survival estimates in the tropics, but this approach is thought to overestimate survival because it does not sample social and age classes with lower survival. We compared the effect of field methods on tropical survival estimates and their relationships with life history traits. Location Sabah, Malaysian Borneo. Time period 2008–2016. Major taxon Passeriformes. Methods We used standard‐effort netting and resighted individuals of all social and age classes of 18 tropical songbird species over 8 years. We compared apparent survival estimates between these two field methods with differing analytical approaches. Results Estimated detection and apparent survival probabilities from standard‐effort netting were similar to those from other tropical studies that used standard‐effort netting. Resighting data verified that a high proportion of individuals that were never recaptured in standard‐effort netting remained in the study area, and many were observed breeding. Across all analytical approaches, addition of resighting yielded substantially higher survival estimates than did standard‐effort netting alone. These apparent survival estimates were higher than for temperate zone species, consistent with latitudinal differences in life histories. Moreover, apparent survival estimates from addition of resighting, but not from standard‐effort netting alone, were correlated with parental effort as measured by egg temperature across species. Main conclusions Inclusion of resighting showed that standard‐effort netting alone can negatively bias apparent survival estimates and obscure life history relationships across latitudes and among tropical species.

Vegetation on ultramafic edaphic ‘islands’ in Kinabalu Park (Sabah, Malaysia) in relation to soil chemistry and elevation - Antony van der Ent; Peter Erskine; David Mulligan; Rimi Repin; Rositti Karim (Plant and Soil, 2016)